Magnetic resonance guided SBRT reirradiation in locally recurrent prostate cancer: a multicentric retrospective analysis - Boldrini, Luca; Romano, Angela; Chiloiro, Giuditta; Corradini, Stefanie; De Luca, Viola; Verusio, Valeria; D’Aviero, Andrea; Castelluccia, Alessandra; Alitto, Anna Rita; Catucci, Francesco; Grimaldi, Gianmarco; Trapp, Christian; et al. (Radiation oncology, 2023)
Reirradiation of prostate cancer (PC) local recurrences represents an emerging challenge for current radiotherapy. In this context, stereotactic body radiation therapy (SBRT) allows the delivery of high doses, with curative intent. Magnetic Resonance guided Radiation Therapy (MRgRT) has shown promising results in terms of safety, feasibility and efficacy of delivering SBRT thanks to the enhanced soft tissue contrast and the online adaptive workflow. This multicentric retrospective analysis evaluates the feasibility and efficacy of PC reirradiation, using a 0.35 T hybrid MR delivery unit.
Gesehen am 04.08.2023